Astute competition [electronic resource] : the economics of strategic diversity - Johnson, Peter , 1956- (Technology, innovation, entrepreneurship, and competitive strategy series, 2007)
The first part of this book aims to provide a rigorous account of the five key strategic building blocks that underpin an analysis of heterogeneous competition. The second part deals with how these strategic concepts, embedded in various analytical tech